Aplicação de água residuária de suinocultura em colunas de solo - Trevisan, Ana Paula (2012)
This paper aimed at assessing the possible effects caused in soil and percolate in columns with the application of different levels of residuary water of swine culture. The experiment was conducted in vegetable house in 15 columns of PVC tubes filled up with layers of 0-5, 5-10, 10-20, 20-40, 40-60 and 60-80 cm of a distroferic red nitrosoil, a very clayish texture. The treatments consisted of crescent doses of residuary water of swine culture. (0, 150, 300, 450 and 600 m3 ha-1 year-1), in only one application, with three repetitions per treatment. It was performed a chemical analysis of the soil and of the percolated material in the beginning and in the end of the experiment. The effect of the application of residuary water of swine culture in relation to the profile of soil promoted alterations in the attributes of soil diminishing the pH and increasing aluminum. About the data before and after the application of ARS this proportioned an increase of Al, H+Al3+, Mg, K, CTC and P, and also provoked decrease in pH and Ca. in the percolated material there was no interaction, therefore not provoking environmental damages in the sub soil waters.